Nothing is Permanent but Change: The Journey to Consolidation and Back - Fritch, Melia E.; Bonella, Laura J.; Coleman, Jason (My University, 2014)
Responding to a staffing shortage and assessment of usage data, eight of Hale Library's nine service desks were consolidated into one service point. Fourteen months later, the Libraries conducted an assessment of the consolidation using reference transaction data, responses to a survey administered to Libraries’ staff, and responses from a student focus group. The assessment revealed many logistical and staffing challenges with the new desk. As a result, a separate service point for reference was created directly outside the consolidated desk. Our statistics indicate that this was a successful change.
Keywords: Reference; Consolidation; Patron service; Assessment; Training; Service desks